Profiles based on attitudes toward public support programs of rural micro entrepreneurs of central Chile - Boza, Sofía; Marcos, Gonzalo; Cortés, Maruja; Mora, Marcos (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
This research aims to contribute to the understanding of the attitudes related to public support programs of micro and small farmers in the central zone of Chile. For this, it was conducted a survey of 126 entrepreneurs in the Commune of Cauquenes, Maule Region, which participate in a support program coordinated by the Municipality together with the Institute of Agricultural Development (Indap). The survey focused on the following issues: respondents’ identification, sociodemographic characteristics, production and business management methods, access to technologies and attitudes about public support programs. It was applied a non-hierarchical cluster analysis to data obtained. The existence of two groups of entrepreneurs was identified: "skeptics" (30.15%) and "receptive" (69.85%), with important differences in their attitudes toward support programs and also in their education level, farm productivity and access to technologies. This leads to the conclusion that, even among producers in vulnerable situations, there are important contrasts that should be incorporated in the design, implementation and evaluation of programs.